miR-24-3p promotes proliferation and inhibits apoptosis of porcine granulosa cells by targeting P27 - Shengjie Shi; Lutong Zhang; Liguang Wang; Huan Yuan; Haowei Sun; Mielie Madaniyati; Chuanjiang Cai; Weijun Pang; Lei Gao; Guiyan Chu (Journal of Integrative Agriculture, 2024)
Ovarian follicle development is associated with the physiological functions of granulosa cells (GCs), including proliferation and apoptosis. The level of miR-24-3p in ovarian tissue of high-yielding Yorkshire×Landrace sows was significantly higher than that of low-yielding sows. However, the functions of miR-24-3p on GCs are unclear. In this study, using flow cytometry, 5-ethynyl-2´-de-oxyuridine (EdU) staining, and cell count, we showed that miR-24-3p promoted the proliferation of GCs increasing the proportion of cells in the S phase and upregulating the expression of cell cycle genes, moreover, miR-24-3p inhibited GC apoptosis. Mechanistically, on-line prediction, bioinformatics analysis, a luciferase reporter assay, RT-qPCR, and Western blot results showed that the target gene of miR-24-3p in proliferation and apoptosis is cyclin-dependent kinase inhibitor 1B (P27/CDKN1B). Furthermore, the effect of miR-24-3p on GC proliferation and apoptosis was attenuated by P27 overexpression. These findings suggest that miR-24-3p regulates the physiological functions of GCs.